2000
DOI: 10.1211/0022357001773742
|View full text |Cite
|
Sign up to set email alerts
|

Do Biocides Select for Antibiotic Resistance?

Abstract: Some similarities exist between bacterial resistance to antibiotics and to biocides, and gram-negative bacteria that have developed resistance to cationic biocides may also be insusceptible to some antibiotics. Outer membrane changes are believed to be responsible for this non-specific increase in resistance. Efflux, another important resistance mechanism, is associated with the qacA/B gene system in staphylococci that confers low-level resistance to cationic agents including chlorhexidine salts and quaternary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 64 publications
0
100
1
Order By: Relevance
“…It has been observed that some bacteria which express increased resistance to antiseptics are generally less susceptible to antibiotics. Outer membrane changes have been believed to be one of the mechanisms responsible for such increased non-specific cross-resistance (Russell 2000). Whether the qac genes are able to directly confer resistance to antibiotics remains to be determined.…”
Section: The Qac Genes and Resistance To Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that some bacteria which express increased resistance to antiseptics are generally less susceptible to antibiotics. Outer membrane changes have been believed to be one of the mechanisms responsible for such increased non-specific cross-resistance (Russell 2000). Whether the qac genes are able to directly confer resistance to antibiotics remains to be determined.…”
Section: The Qac Genes and Resistance To Antibioticsmentioning
confidence: 99%
“…The link between the qac genes and macrolide inactivation genes was revealed in Aeromonas hydrophila (Poole et al 2006) as well as in microflora from a wastewater treatment plant (Szczepanowski et al 2004). Therefore, the use of various cationic biocides may be also responsible for the selection of bacteria resistant to antibiotics (Russell 2000;Hegstad et al 2010). …”
Section: The Qac Genes and Resistance To Antibioticsmentioning
confidence: 99%
“…The recurrent use of chemical disinfectants and also the inadequate disinfection strategies impose selective pressure and contribute to the emergence of resistance among microorganisms (Russell 2000). Resistant microorganisms have been responsible for the failure of many disinfection programs, and therefore for many contaminations in industrial, environmental and biomedical settings (Chorianopoulos et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous and uncontrolled usage of antibacterial agents has no doubt contributed significantly to bacterial resistance, and there are many similarities between the ways in which bacteria are able to resist antibiotics and biocides (24). These mechanisms include decreased drug accumulation, decreased permeability, modification of the target, and modification of the antibiotic itself (20).…”
mentioning
confidence: 99%